Investigating Social Capital Levels Among Small Holder Maize Farmers in the Kwahu North District, Ghana - Tham-Agyekum, Enoch Kwame; Nimoh, Fred (Asian Journal of Agriculture and Rural Development, 2013)
The process of community development has often been linked with social capital, in recent times. Using a household-level survey data, this study investigates social capital levels among small-holder maize farmers in the Kwahu North district of the Eastern region of Ghana. The results of the study show that there exists a low level of social contacts among farmers in the study area. However, there are moderate levels of information flow, access to resources and attendance to community activities among the sampled farmers. The level of social capital was found to be relatively high, as a majority of the respondents were at the moderate level and beyond. The study recommends that there is the need for behavioural change among farmers, particularly with their social contacts, as this could help further enhance their social capital and hence their livelihoods.